The Aguas Zarcas carbonaceous chondrite: bolide, fall and recovery of an extraordinary CM2 type meteorite - Lücke, Oscar H. (2019)
On April 23rd, 2019 at 21:08 local time, a fireball was observed crossing the night sky of central Costa Rica with a general southeast to northwest direction, in an event registered by both witnesses and cameras. A subsequent explosive sound (fragmentation in the atmosphere) was reported near San Carlos, followed by a meteorite shower in the districts of Aguas Zarcas and La Palmera, of San Carlos. The first recovered fragment (1071 g) came from a house near La Caporal in Aguas Zarcas, where the impact bored a hole in the ceiling breaking the meteorite in smaller pieces adding up to a total weight of 1152 g. In the following days several other fragments were recovered towards the northwest of Aguas Zarcas, in the towns of La Cocaleca, Santa Rosa, and La Palmera, with weights ranging from <1g to 1875 g. The total recovered mass of the meteorite was estimated in roughly 30 kg. After proper revision by the Meteoritical Society, the official name “Aguas Zarcas Meteorite” was approved on May 30th, 2019. The main masses of the meteorite, in excess of ~50 g, show regmaglypts (some with iridescent surfaces). Other fragments display drop, platy, and elliptical forms, with aerodynamic patterns, and showing a frontal dome. The inner parts of the analyzed specimens show chondrules on varying areal percentages, within a dark-gray to black matrix. Calcium-Aluminum rich inclusions (CAI), sub-millimetric crystals of plagioclase, olivine, and sulphide and metallic flakes are also present in the matrix. A clear fusion crust is evident in some fragments showing cooling microfractures. It is slightly magnetic and expels a particular organic-like odor. Geochemical and isotopic analyses performed at the Universities of Costa Rica, Arizona and Nuevo Mexico, among others, and the observed textural characteristics of the meteorite, indicate that it belongs to the Carbonaceous Chondrite classification of rocky meteorites, type CM2 which entails the presence of hydrated minerals within a fine matrix composed of carbon, and nickel-rich sulphides components. CM2 meteorites also show general compositions and oxygen isotope compositions similar to the primitive solar nebula. Carbonaceous chondrites represent only ~4% of the total recovered meteorites worldwide and they preserve the geochemical, isotopic, and mineralogical composition of the first millions of years of the history and evolution of the Solar System, making the Aguas Zarcas Meteorite an extraordinary event, and sparking national and international scientific interest.